(untitled) (Revista Apotheke, 2024)
This work reflects on the first results of artistic practice, obtained within the scope of the artistic project Lugar Habitado and presented in the solo exhibition Caminho Entre Duas Linhas. Through the creation of a pedestrian route in Lisbon, the act of walking is presented as a research resource for artistic practice and expression, which allows for a reflection on the relationship between the territory, memory and the construction of the identity of the individuals who inhabit it. The works produced demonstrate an interaction between the act of walking and the creation of individual and collective narratives, highlighting the role of memory in the construction of a sense of belonging. This is an exhibition that seeks to place the artist’s personal relationship with the territory in dialogue with others, contributing to the construction of a collective identity.